Anterior tooth growth periods in Neandertals were comparable to those of modern humans - Guatelli-Steinberg, Debbie (National Academy of Sciences, 2005)
A longstanding controversy in paleoanthropology surrounds the question of whether Neandertals shared the prolonged growth periods of modern humans. To address this question, this investigation compares the duration of enamel formation in Neandertals with that of three comparative modern human groups. Because dental and somatic growth are correlated with each other, dental growth periods are indicative of overall periods of growth. Growth increments on the anterior teeth of Neandertals, modern Inuit, and modern people from Newcastle and southern Africa were counted and their means compared. In addition, potential variation in the time spans represented by growth increments was considered and incorporated into the analysis of enamel formation times. These analyses show that Neandertal imbricational enamel formation times, although likely to have been faster than those of the Inuit, are not likely to have been faster than those of the Newcastle sample and for some teeth are clearly slower than those of the southern African sample. Thus, Neandertal tooth growth and, by extension, somatic growth, appears to be encompassed within the modern human range of interpopulation variation.